Reagent and Catalyst Design for Asymmetric Hypervalent Iodine Oxidations - Berthiol, Florian (Synthesis, 2015)
In this review are compiled the different possible transformations using environmentally benign chiral hypervalent iodine reagents and catalysts. Herein is presented an overview of asymmetric oxidation of sulfides to sulfoxides, oxidation of alkenes, α-functionalization of carbonyl compounds and dearomatization reactions.1 Introduction2 Chiral Hypervalent Iodine Reagents3 Oxidation of Sulfides to Sulfoxides4 Oxidation of Alkenes5 α-Functionalization of Carbonyl Compounds6 Dearomatization Reactions7 Conclusion
Keywords: hypervalent iodine; asymmetric transformations; homogeneous organocatalysis; oxidations; carbon–carbon bond formations; carbon–heteroatom bond formations